2018
DOI: 10.2147/ijn.s165876
|View full text |Cite
|
Sign up to set email alerts
|

Novel application of trimethyl chitosan as an adjuvant in vaccine delivery

Abstract: The application of natural carbohydrate polysaccharides for antigen delivery and its adjuvanation potential has garnered interest in the scientific community in the recent years. These biomaterials are considered favorable candidates for adjuvant development due to their desirable properties like enormous bioavailability, non-toxicity, biodegradability, stability, affordability, and immunostimulating ability. Chitosan is the one such extensively studied natural polymer which has been appreciated for its excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 109 publications
(104 reference statements)
0
50
0
3
Order By: Relevance
“…14 Chitosan (CS) is a linear cationic polysaccharide that is obtained by the partial deacetylation of chitin, the second most abundant polysaccharide. [15][16][17] Structurally, CS consists of β-(1-4) N-acetyl-d-glucosamine and β-(1,4)-2amino-2-deoxy-D-glucopyranose units. 18 Previous studies have demonstrated the applications of CS in the field of medicine and pharmaceutical research due to their mucoadhesive properties as well as their antibacterial, anticancer and permeation-enhancing ability for targeted drug and protein delivery.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…14 Chitosan (CS) is a linear cationic polysaccharide that is obtained by the partial deacetylation of chitin, the second most abundant polysaccharide. [15][16][17] Structurally, CS consists of β-(1-4) N-acetyl-d-glucosamine and β-(1,4)-2amino-2-deoxy-D-glucopyranose units. 18 Previous studies have demonstrated the applications of CS in the field of medicine and pharmaceutical research due to their mucoadhesive properties as well as their antibacterial, anticancer and permeation-enhancing ability for targeted drug and protein delivery.…”
Section: Introductionmentioning
confidence: 99%
“…18 Previous studies have demonstrated the applications of CS in the field of medicine and pharmaceutical research due to their mucoadhesive properties as well as their antibacterial, anticancer and permeation-enhancing ability for targeted drug and protein delivery. 17,19 Notably, a composite of CS with other polymeric material has proven useful in regenerative medicine. 20 However, one drawback in the applicability of CS is the poor solubility at neutral and alkaline conditions, which decreases drug delivery efficiency at pH values above 6.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These characteristics determine their chemical and biological properties. The main reactions involve the primary amino group, a powerful nucleophile that can undergo N acylation, quaternization, reductive amination and Schiff reactions among others, allowing introducing different functional groups in the molecule and therefore modifying their properties [10][11][12][13][14][15][16]. Various alternatives to increase the solubility of chitosan have been studied.…”
Section: Introductionmentioning
confidence: 99%